Effect of fluorescent staining on size measurements of polymeric nanoparticles using DLS and SAXS. Issue 23 (30th October 2015) - Geißler, D.; Gollwitzer, C.; Sikora, A.; Minelli, C.; Krumrey, M.; Resch-Genger, U.
Abstract : The influence of fluorescence on nanoparticle size measurements using dynamic light scattering (DLS) and small angle X-ray scattering (SAXS) was investigated. Abstract : The influence of fluorescence on nanoparticle size measurements using dynamic light scattering (DLS) and small angle X-ray scattering (SAXS) was investigated. For this purpose, two series of 100 nm-sized polymer nanoparticles stained with different concentrations of the fluorescent dyes DY555 and DY680 were prepared, absorbing/emitting at around 560 nm/590 nm and 695 nm/715 nm, respectively. SAXS measurements of these particle series and a corresponding blank control (without dye) revealed similar sizes of all particles within an uncertainty of 1 nm. DLS measurements carried out at three different laboratories using four different DLS instruments and two different laser wavelengths, i.e., 532 nm and 633 nm, revealed also no significant changes in size (intensity-weighted harmonic mean diameter, Z -Average) and size distribution (polydispersity index, PI) within and between the two dye-stained particle series and the blank sample. Nevertheless, a significant decrease of the detected correlation coefficients was observed with increasing dye concentration, due to the increased absorption of the incident light and thus, less coherent light scattering. This effect was wavelength dependent, i.e. only measurable for the dye-stained particles that absorb at the laser wavelength used for the DLS measurements.